The Ironic Legacy of an Opus Dei Bishop: Native Priests and Andean Catholicism in Postconflict Apurímac, Peru. (September 2019) - Lee, Christine
Since the end of the civil war, the diocese of Abancay in the south-central Peruvian Andes has produced a clergy made up entirely of men born and raised in the diocese where they now work. Yet, ironically, this diocese was specifically criticized by the Truth and Reconciliation Commission for its lack of engagement with local Andean populations. Abancay is a politically and theologically conservative diocese strongly influenced by the Opus Dei bishop who trained this generation of native clergy, but it is also a diocese in the process of forging a new relationship between Andeanness and institutional Catholicism. Desde el final de la guerra civil, la diócesis de Abancay, en los Andes peruanos del centro-sur, ha producido un clero formado exclusivamente por hombres nacidos y criados en la diócesis donde trabajan actualmente. Sin embargo, irónicamente, esta diócesis fue criticada específicamente por la Comisión de la Verdad y la Reconciliación por su falta de compromiso con las poblaciones andinas locales. Abancay es una diócesis política y teológicamente conservadora fuertemente influenciada por el obispo perteneciente al Opus Dei que formó a esta generación de clérigos nativos, pero también es una diócesis en el proceso de forjar una nueva relación entre la identidad andina y el catolicismo institucional.